2014
DOI: 10.1242/jeb.108167
|View full text |Cite
|
Sign up to set email alerts
|

Spatial coordination of foot contacts in unrestrained climbing insects

Abstract: Animals that live in a spatially complex environment such as the canopy of a tree, constantly need to find reliable foothold in threedimensional (3D) space. In multi-legged animals, spatial co-ordination among legs is thought to improve efficiency of finding foothold by avoiding searching-movements in trailing legs. In stick insects, a 'targeting mechanism' has been described that guides foot-placement of hind-and middle legs according to the position of their leading ipsilateral leg. So far, this mechanism ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 38 publications
0
33
1
Order By: Relevance
“…For example, hair plates at proximal leg joints monitor the movement ranges of insect legs (Cruse et al, 1984;Markl, 1962;Schmitz, 1986;Wendler, 1964;Wong and Pearson, 1976), and chordotonal organs monitor the current position and movement of individual leg segments (Burns, 1974;Field and Matheson, 1998;Hofmann et al, 1985;Mamiya et al, 2018;Zill, 1985). Signals from these proprioceptors are critical for the spatial coordination of the leg (Bässler, 1977;Couzin-Fuchs et al, 2015;Mendes et al, 2013;Theunissen et al, 2014). The few changes in kinematics observed in the present study, such as the magnitude of the extension angle ( Fig.…”
Section: Motor Control Of Level and Incline Walkingmentioning
confidence: 61%
See 1 more Smart Citation
“…For example, hair plates at proximal leg joints monitor the movement ranges of insect legs (Cruse et al, 1984;Markl, 1962;Schmitz, 1986;Wendler, 1964;Wong and Pearson, 1976), and chordotonal organs monitor the current position and movement of individual leg segments (Burns, 1974;Field and Matheson, 1998;Hofmann et al, 1985;Mamiya et al, 2018;Zill, 1985). Signals from these proprioceptors are critical for the spatial coordination of the leg (Bässler, 1977;Couzin-Fuchs et al, 2015;Mendes et al, 2013;Theunissen et al, 2014). The few changes in kinematics observed in the present study, such as the magnitude of the extension angle ( Fig.…”
Section: Motor Control Of Level and Incline Walkingmentioning
confidence: 61%
“…As in level walking, the hindleg closely followed the middle leg on the same side of the body, which in turn followed the front leg ( Fig. 2B; see also Cruse, 1979;Dean and Wendler, 1983;Theunissen et al, 2014). Walking speeds ranged from 23 to 85 mm s −1 (∼0.3-1.1 body lengths s −1 ; defined as the mean speed of the COM over the step cycle).…”
Section: Kinematics Are Similar On Inclinesmentioning
confidence: 78%
“…In a recent study, we have shown that a 'targeting mechanism' is part of the spatial coordination of legs in three-dimensional space in Carausius (Theunissen et al, 2014c). A preliminary look at the accuracy and precision of hind leg targeting towards the position of the middle leg in other species suggests that this mechanism works the same in climbing Aretaon and Medauroidea (Theunissen et al, 2014b).…”
Section: Use Of Thorax Anglesmentioning
confidence: 89%
“…Ground contact was determined based on the velocity of the tibia-tarsus joints and the distance to the surface (see also, Theunissen et al, 2014c), The velocity had to decrease below a certain threshold for at least eight consecutive frames (40 ms). The threshold was set to 25 mm s −1 for Carausius and Aretaon, and to 50 mm s −1 for Medauroidea.…”
Section: Foot Contacts and Step Lengthmentioning
confidence: 99%
“…Regarding coordinate transformation among limbs, several studies have demonstrated this to occur in stick insects, including standing (Cruse, 1979), walking (Dean and Wendler, 1983) and climbing animals (Theunissen et al, 2014). Targeting behavior of legs has been transferred into models of motor control.…”
Section: Introductionmentioning
confidence: 99%